First detection of Kashmir bee virus in the UK using real-time PCR - Ward L. (2014)
Kashmir bee virus (KBV) often persists in bees as a covert infection with no apparent symptoms. The virus can switch to become an overt lethal infection, especially in the presence of Varroa mites. Although the virus is distributed worldwide, it was thought to be absent from the UK. A real-time PCR assay was developed for specific detection of KBV. No cross-reaction was observed with other bee viruses. KBV was successfully amplified from different life stages of honey bees and from a wasp and bumble bee. Using the real-time PCR assay, a survey of hives was conducted in England and Wales to investigate the presence and geographical distribution of the virus. KBV was detected within three colonies at two locations. The virus titre in the positive samples was quantified and found to contain similar levels to other bees with covert KBV infection. We conclude that KBV is present in the UK and cannot now be considered an exotic disease. The discovery of KBV in the UK has major significance for import policies. © INRA/DIB-AGIB/ EDP Sciences, 2007.